Pemanfaatan Digital Marketing sebagai Media Pemasaran Produk Kelompok Usaha Keripik RK di Kelurahan 13 Ulu Palembang - Sartika, Dewi; Saluza, Imelda; Roswaty (Universitas Muhammadiyah Malang, 2023)
Partner in this activity is Raja Keripik Cassava Chips (RK) Business Group which has been running its business for 3 years. It is located in 13 Ulu Palembang. Product sold by partner is cassava chips with original and hot balado variants. The product produced has more special characteristics than another similar product. The product is called